Non-invasive diagnostic methods of the liver fibrosis in patients with overweigh and obesity - Nadiia Gavryliuk; Ihor Hospodarskyy; Oksana Prokopchuk; Olga Namisniak; Mykhailo Havrylyuk (Kazimierz Wielki University, 2021)
One of the biggest problems of modern medicine is the difficulty in early diagnostic and effective treatment of HCV infection due to its wide distribution, latent form and terrible consequences as a formation of liver cirrhosis (CP) and hepatocellular carcinoma (HCC). It is important to mention, that the rate of progression of liver fibrosis. It is an important medical and social problem that the number of patients with NAFLD, overweight and obesity is constantly increases [9]. Due to the high prevalence of NAFLD and CHC, these two pathologies will progress and contribute to the progression of fibrosis, and depending on the genome of the virus and metabolic syndrome. There is a high risk of developing CP and HCC even after achieving a stable virological response. The main aim of our investigation was to assess the stages of fibrosis by using non-invasive methods for patients with overweight and obesity who being treated for HCV infection (with posthepatic fibrosis).